Circles of Truth in Curriculum-making for Science in the Primary Classroom: Keeping in Mind Simplicity, Compassion and the ‘Faded Green Textbook’ - Tassell, Alison Barbara (Curtin University, 2017)
My inquiry explores a curriculum of simplicity and compassion that might encourage primary teachers to accept responsibility for teaching science. I have faith primary teachers have the pedagogic competence to kindle the light of science to shine in the hearts of their students and value this possibility. To write this curriculum I found the need for mutual trust, pedagogy, and integrity in the interacting and intersecting circles of truth entwining curriculum-writer, teachers and students.